Avaliação clínica e parasitológica da coinfecção experimental por Leishmania (Leishmania) amazonensis e Leishmania (L.) infantum em hamster (Mesocricetus auratus) - Jordanna Luíza de Lima Celeste (2015)
In Brazil, there are two clinical forms of leishmaniasis: Visceral Leishmaniasis (VL) and Tegumentary Leishmaniasis (LT). The VL has the etiologic agent Leishmania (L.) infantum (= L. (L.) chagasi) affecting mainly organs such as the spleen and liver, and TL has several clinical manifestations and has as etiological agents several species, including L. (L.) amazonensis, causing skin lesions. It is known that in country there are overlapping areas of these two species, which may facilitate the occurrence of coinfection. Although it is more common VL caused by L. infantum and TL caused by L. amazonensis, in Brazil there are reports of visceralization caused by L. amazonensis in humans and dogs from urban areas. Hamsters are considered good experimental models in Leishmania spp infections and were used in this study to a better understanding of this type of infection. Thus, the species L. (L.) infantum (MCAN/BR/2002/BH401) and L. (L.) amazonensis (IFLA/BR/1967/PH8) were inoculated separately and simultaneously in these animals by intraperitoneal and subcutaneous routes, and they were followed for 90 days. The route of inoculation had no influence on the clinical changes of infection by L. infantum or L. amazonesis, however, L. infantum has more typical establishment intraperitoneally while L. amazonensis subcutaneously. L. amazonensis has the capacity to invade the spleen and liver earlier than L. infantum in all situations evaluated, but L. infantum can prevail over time. The coinfection was more severe, with L. amazonensis causing early splenomegaly and skin lesions in the inoculum site and disseminated.